Pharmacokinetic profile of dalfampridine extended release: clinical relevance in patients with multiple sclerosis. (December 2013) - Weir, Scott; Torkin, Risa; Henney III, Herbert R.
Abstract Background In January 2010, dalfampridine extended release tablets (dalfampridine-ER [Ampyra*]; prolonged-, modified- or sustained-release fampridine [Fampyra†] in some countries), 10 mg to be administered twice daily approximately 12 hours apart, were approved by the US Food and Drug Administration. This was the first drug indicated to improve walking in patients with MS. Scope Publications describing the pharmacokinetics of dalfampridine-ER or the immediate release formulation were identified from a search of PubMed through June 2012 using the search terms 'dalfampridine OR fampridine OR 4-aminopyridine' AND 'pharmacokinetics' and were supplemented with unpublished studies made available by Acorda Therapeutics Inc. Findings Pharmacokinetic studies show dose proportionality, with dalfampridine-ER having a more favorable profile than immediate-release dalfampridine. With twice-daily dosing of dalfampridine-ER, time to peak plasma concentration (3.2–3.9 hours) and apparent terminal plasma half-life (5.6–6.4 hours) are approximately twice those of immediate-release formulations, with comparable overall exposure and peak plasma concentrations (21.6 ng/mL) that were maintained at levels approximately 50% lower than immediate release. Steady state is achieved within 39 hours; pharmacokinetics are predictable based on single dosing. Trough plasma concentrations of 13–15 ng/mL are required to maintain efficacy. Renal excretion is predominantly as unchanged compound, and renal clearance in healthy individuals exceeds the glomerular filtration rate. Since dalfampridine-ER exposure increases with renal impairment, it is contraindicated in patients with moderate or severe impairment in the US, and in patients with any renal impairment in the European Union. Conclusions Dalfampridine-ER has low protein binding, is not a substrate for p-glycoprotein and does not affect CYP450 enzymes, suggesting a low potential for drug–drug interactions. Because of the narrow therapeutic range and risk of adverse events, including seizure, with increasing plasma concentrations, the recommended dose and regimen of dalfampridine-ER should not be exceeded and not be used with other dalfampridine formulations. A limitation of this review is that it includes some data that have not yet been published.